The Integration of Modern Psychology in Malek Bennabi’s Methodology of Studying Civilization - Benlahcene, Badrane (Afkar: Jurnal Akidah dan Pemikiran Islam, 2024)
This research aims to analyze the integration of psychology in the methodology of Malek Bennabi in studying civilization. In order to achieve this goal, this study adopts an analytical approach to his writings. The study concluded that Bennabi, in his endeavor to study civilization and his adoption of civilization as an analytical unit for the problems of the Islamic world, constructed his civilizational perspective by integrating various sciences, especially the humanities and social sciences, in an interdisciplinary way. Hence, psychology was one of the sciences integrated in his methodology for studying civilization. The integration of psychology in Bennabi’s writings entails an interest in the pioneers of psychology, their concepts, and their methodologies both critically and implicatively.